REGION OF PRESPA AMONG THREE COUNTRIES - Meri Stojanova (EtnoAntropoZum, 2016)
According to its historical and cultural past and the way of its’ reflection toward the future the region of Prespa becomes one of the most interesting regions in Macedonia. Its heritage belongs to three neighbouring countries that cause hardship, but in the same time it opens possibilities.